Exploring The Influence of Personality Traits and AI MediatorDesign on ‎Dispute Resolution: The Mediating Role ofMediator Function and ‎ModeratingEffect of Dispute Type - Bharadwaj , Pradeep Kumar; Ojha, Dr. Megha; Podile, Dr. Venkateswara Rao (International Journal of Accounting and Economics Studies, 2026)
This study investigates the role of individual personality traits and AI mediator design features in ‎influencing dispute resolution effectiveness, with a focus on the mediating role of the mediator's ‎function and the moderating effect of dispute type. Drawing from the Big Five personality ‎framework and human–AI interaction literature, a structural equation model (SEM) was ‎employed using a sample of 300 respondents engaged in simulated dispute resolution scenarios. ‎The analysis revealed that both personality traits (e.g., openness, conscientiousness, and ‎emotional stability) and AI mediator design elements (usability, transparency, perceived fairness, ‎and adaptability) significantly influence dispute resolution outcomes. Importantly, the mediator’s ‎role—defined through neutrality, facilitation, and communication style—was found to mediate ‎these effects. Furthermore, multi-group analysis showed that the strength of this mediation ‎pathway varies depending on the type of dispute, with the strongest effects observed in family ‎and workplace conflicts.‎Model fit indices (CFI = 0.962, TLI = 0.950, RMSEA = 0.061, SRMR = 0.041) confirmed a ‎good fit. The results underscore the necessity of designing context-aware, user-centric AI ‎systems and integrating psychological profiles for optimized dispute resolution processes. The ‎study contributes to the growing discourse on AI in legal and organizational contexts and ‎provides a framework for the development of adaptive, ethical, and effective AI mediation tools‎.
Keywords: AI Mediator Design; Personality Traits; Dispute Resolution; Mediator Function; Dispute Type ‎Moderation